Fatores de risco, disfunção da barreira intestinal e co-patógenos de infecções subclínicas causadas por Campylobacter jejuni em crianças da cidade de Fortaleza-CE, Brasil - Veras, Herlice do Nascimento (2021)
Introduction: Campylobacter spp. is one of the main causes of bacterial infection caused by the ingestion of water or food contaminated in the world. Campylobacter jejuni is the most prevalent species being one of the main reasons of gastroenteritis in humans. Aim: We wanted to investigate risk factors, intestinal barrier dysfunction and copathogens of subclinical infection caused by Campylobacter jejuni in children from the Fortaleza - CE, Brazil. Material and Methods: A Nested case-control study has been conducted from a multicentric longitudinal cohort study entitled “Etiology, Risk Factors and Interactions of Enteric Infections and Malnutrition and its Consequences for Children’s Health (MAL-ED)”, conducted between August 2010 and September 2013. The study included 233 children with ages between 0-24 months of age who were divided into two groups: case group with children who had positive samples for C. jejuni, and control group with children who had negative samples for C. jejuni. The bacterial diagnosis was performed with extracted fecal bacterial DNA using the TAC qPCR platform, which unspecifically diagnosed C. jejuni / C. coli, followed by the specific diagnosis of C. jejuni by conventional PCR. The evaluation of anthropometric measures WAZ, WHZ and HAZ was performed. We also investigated 20 virulence genes of C. jejuni through uniplex and multiplex PCR. We evaluated intestinal barrier integrity by HLPC detection of Lactose/Mannitol (L/M) and the immunoenzymatic assays for alpha-1-antitrypsin (AAT) and the inflammatory biomarkers of Myeloperoxidase (MPO) and Neopterin (NEO). Results: 27,03% (63/233) of these children had a positive diagnosis only for C. jejuni. The lack of breast-feeding alone displayed a risk factor for C. jejuni infections on the children (P <0,0001; OR 11,25; IC 95% 3,664 – 35,66). The usage of filters for water treatment was not enough to prevent infections by C. jejuni (P = 0,03; OR 3,389; IC 95% 1,166 – 9,064). In addition, 33,33% (21/63) of the children presented more than one positive sample for this pathogen. Children from the case group up to 15 months had a change on the intestinal permeability through the analysis of ATT (P = 0,037; IC 95% -0,2509 - 0,007929). The cheW gene was the most prevalent (84,13% - 53/63), but the gene pVir had no prevalence (0% - 0/63). Coinfection of EPEC and C. jejuni was the most prevalent (44,44% - 28/63) and, concomitantly, we found a reduction of WHZ of the children who had this coinfection (P = 0,0491; IC 95% 0,001733 - 0,8458). EAEC was the second most prevalent copathogen (31,80% - 20/63), which impaired intestinal impermeability through the L/M ratio (P = 0,0024; IC 95% -0,1639 -0,03634) and AAT (P = 0,0103; IC = -0,3850 - 0,05389), in addition to the correlation with inflammation through the detection of NEO (P = 0,047; IC 95% -4002 - 2626). Conclusion: There was a high rate of subclinical infections caused by C. jejuni, since the presence of this pathogen did not influence growth deficit, or cause inflammation, but altered the intestinal barrier function. C. jejuni caused more significant damage, such as growth deficit, inflammation and changes in intestinal barrier markers when in association with the cotathogens EPEC and EAEC, characterizing the presence of environmental enteric dysfunction.